Evolution of theory of system cycles of capital accumulation - A. V. Avramenko (Путеводитель предпринимателя)
The article describes the evolution of the theory of systemic cycles of capital accumulation (SCCA) and its related approaches. These theories try to analyze the presence of the phenomenon change phases globalization and the strengthening of international relations and phases of regionalization and degradation of international relations in the global socio-economic and political development. It is characteristically for the present historical moment. This article describes the background of genesis SCCA theory, basic ideas and approaches this theory, the stages of its development.